Mutational analysis of the substrate specificity of Escherichia coli penicillin binding protein 4. - Clarke,TB; Kawai,F; Park,S-Y; Tame,JRH; Dowson,CG; Roper,DI (Biochemistry, 2009)
Escherichia coli PBP4 is the archetypal class C, low molecular mass penicillin binding protein (LMM-PBP) and possesses both dd-carboxypeptidase and dd-endopeptidase activity. In contrast to other classes of PBP, class C LMM-PBPs show high dd-carboxypeptidase activity and rapidly hydrolyze synthetic fragments of peptidoglycan. The recently solved X-ray crystal structures of three class C LMM-PBPs (E. coli PBP4, Bacillus subtilis PBP4a, and Actinomadura R39 dd-peptidase) have identified several residues that form a pocket in the active site unique to this class of PBP. The X-ray cocrystal structure of the Actinomadura R39 DD-peptidase with a cephalosporin bearing a peptidoglycan-mimetic side chain showed that residues of this pocket interact with the third position meso-2,6-diaminopimelic acid residue of the peptidoglycan stem peptide. Equivalent residues of E. coli PBP4 (Asp155, Phe160, Arg361, and Gln422) were mutated, and the effect on both DD-carboxypeptidase and DD-endopeptidase activities was determined. Using N-acetylmuramyl-L-alanyl-gamma-D-glutamyl-meso-2,6-diaminopimelyl-D-alanyl-D-alanine as substrate, mutation of Asp155, Phe160, Arg361, and Gln422 to alanine reduced k(cat)/K(m) by 12.7-, 1.9-, 24.5-, and 13.8-fold, respectively. None of the k(cat) values deviated significantly from wild-type PBP4. PBP4 DD-endopeptidase activity was also affected, with substitution of Asp155, Arg361, and Gln422 reducing specific activity by 22%, 56%, and 40%, respectively. This provides the first direct demonstration of the importance of residues forming a subsite to accommodate meso-2,6-diaminopimelic acid in both the DD-carboxypeptidase and DD-endopeptidase activities of a class C LMM-PBP.